2017
DOI: 10.1016/j.immuni.2017.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Elicitation of Robust Tier 2 Neutralizing Antibody Responses in Nonhuman Primates by HIV Envelope Trimer Immunization Using Optimized Approaches

Abstract: SummaryThe development of stabilized recombinant HIV envelope trimers that mimic the virion surface molecule has increased enthusiasm for a neutralizing antibody (nAb)-based HIV vaccine. However, there is limited experience with recombinant trimers as immunogens in nonhuman primates, which are typically used as a model for humans. Here, we tested multiple immunogens and immunization strategies head-to-head to determine their impact on the quantity, quality, and kinetics of autologous tier 2 nAb development. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

36
396
3
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 296 publications
(436 citation statements)
references
References 40 publications
36
396
3
1
Order By: Relevance
“…This observation is consistent with the likelihood that bNAb epitopes are conserved for functional reasons, with escape likely requiring compensatory mutations [97, 110], and suggests that slower viral escape supports the development of bNAbs through prolonged exposure to antigen [96, 97, 110, 111]. This hypothesis is further supported by the demonstration in vaccine studies that extended antigen availability enhances germinal center activity and resulting neutralizing Ab responses [112, 113]. …”
Section: The Role Of Viral Variants In Selecting Bnabssupporting
confidence: 67%
See 1 more Smart Citation
“…This observation is consistent with the likelihood that bNAb epitopes are conserved for functional reasons, with escape likely requiring compensatory mutations [97, 110], and suggests that slower viral escape supports the development of bNAbs through prolonged exposure to antigen [96, 97, 110, 111]. This hypothesis is further supported by the demonstration in vaccine studies that extended antigen availability enhances germinal center activity and resulting neutralizing Ab responses [112, 113]. …”
Section: The Role Of Viral Variants In Selecting Bnabssupporting
confidence: 67%
“…However, during infection bNAbs develop in a highly competitive environment, and immunization studies showed that autologous neutralizing titers were not enhanced by reduction of V3 responses [113, 134]. Additionally, two elegant studies recently showed that most GCs retain substantial clonal diversity during affinity maturation of complex antigens [135, 136].…”
Section: Leveraging Studies Of Infection For Vaccine Design: What Arementioning
confidence: 99%
“…We have observed this phenomenon for several antidrug vaccines, including a fentanyl vaccine, 7 an oxycodone vaccine, 14 and a methamphetamine vaccine, 8 and this may be the result of a shortened vaccination schedule. 15 Antibody titers detected in the admixture were approximately half the level detected in the individual Her-KLH vaccine, as predicted based on the amount of Her-KLH immunoconjugate employed in each group (Table 1), but antibody affinity remained at similar levels. This trend was also observed for fentanyl antibodies in the admixture vaccine group by week 5 (Table 2).…”
Section: Resultsmentioning
confidence: 51%
“…Sporadic studies more than a decade ago found that controlled release of antigen over a longer period of time could result in stronger immune responses than conventional bolus injections [911]. More recent studies have revisited this concept with substantial success [1214]. Here we describe several mechanisms through which sustained antigen availability may modulate the GC response to enhance the humoral response.…”
Section: Introductionmentioning
confidence: 93%
“…Indeed, continuous antigen release over 1–2 weeks using osmotic pumps in mice resulted in higher frequencies of GC Tfh, Tfh and GC B cells [12]. Strikingly, non-human primates (NHPs) immunized with HIV Env via two week osmotic pumps had dramatically increased autologous HIV nAbs compared to animals given a conventional bolus immunization [14]. Furthermore, HIV nAbs also developed in osmotic pump immunized animals more rapidly than conventional animals, suggesting that extended antigen release can accelerate the generation of GC B cells capable of neutralizing HIV.…”
Section: Tfh Cell Help and Affinity Maturationmentioning
confidence: 99%